الدولة في المجال السياسي العربي - نقاش حول الخلفيات والأسس - أمينة مزراق (المسيلة, 2018)
يحوز موضوع "الدولة" أهمية كبرى باعتباره البؤرة التي تحدد علم السياسة، وهي الأهمية التي تشتد عند أقصى حدودها عند دراسة هذه الظاهرة ضمن المجال السياسي العربي، على اعتبار أن ذلك من شأنه أن يؤدي إلى إيجاد تفسير لحالة التأزم والاضطراب السياسي المزمن الذي يشهده هذا المجال. وهو المجال الذي استطاع أن يفرز لنا نمطا جديدا من الدولة خاصا بالحالة العربية، أين يضعف مفهوم الدولة الرمزي والمجرد ويقوى في المقابل منه مفهوم السلطة المادية، وبقدر ما تضعف الأولى تقوى الثانية ليتشكل لدينا مفهوم جديد هو الدولة/السلطة وليس الدولة/الدولة أو الدولة/القيمة. وهو المفهوم الذي كان ضامنا لاستمرار افتراض "قوة الدولة العربية" في مقابل تراجع افتراض "ضعفها ومآلات تفكيكها وسقوطها" وهي القوة التي تستمدها هذه الدولة من ضعف مجتمعاتها على المستوى الداخلي من جهة، ومن ضعفها هي ذاتها-الدولة- مقارنة بمثيلاتها من الدول الغربية على المستوى الدولي من جهة أخرى. وهو الافتراض الذي أثبت صموده بناءا على النتائج والمعطيات التي أفرزتها دولة ما بعد الحراك السياسي والاجتماعي- مطلع 2011- في المجال السياسي العربي والتي أكدت مرة أخرى قدرتها على الاستمرار والبقاء رغم التناقضات التي تنطويها. وسنسعى من خلال هذه الأطروحة إلى تبني ذات الافتراض في معالجة ظاهرة تناقض الدولة العربية في مقابل قدرتها على الاستمرار، وهي الأطروحة التي حكم ترتيب أجزائها ضمن ما يتفق عليه علميا في أن البحث في أي موضوع لايخرج عن الصلة العضوية القائمة بين: اللغة والفكر والواقع، فإذا كنا قد بدأنا باللغة التي أثبتت الخصوصية المفاهيمية لاصطلاح الدولة في الحالة العربية، فذلك لكي نصل إلى الفكر الذي يسند هذا المفهوم من الناحية النظرية، وهو الفكر الذي دلنا بدوره على واقع هذه الدولة المتناقض على اعتبار أن الفكر هو مجرد انعكاس لهذا الواقع، والتشخيص السليم لهذا الواقع هو ما يفرض علينا العودة للفكر مرة أخرى، وذلك في سبيل فتح مجال لإعادة التناظر حول مفهوم الدولة في الحالة العربية وذلك بما يتوافق والأولوية التي يفرضها واقع الدولة اليوم ضمن المجال السياسي العربي. Abstract Possession of the subject of great importance to the state as a focus that determine science policy, which is critical of much at the maximum at the border to study this phenomenon within the Arab political sphere On the grounds that it would lead to find an explanation for the case of chronic crisis and political turmoil witnessed in this area. An area in which it was able to sort out for us a new type of state special Arab situation, where weakens the concept of symbolic and abstract state and strengthens the other hand the concept of physical power, as far as weakening first increase second force to shape our new concept is the state-power and not the state-state or state -the value. A concept that was a guarantor for the continuation of the presumption of "the power of the Arab state" in return for the decline assumption "weakness and malate dismantled and Fall," a force that derive this state of weakness of their societies at the internal level on the one hand, and its weakness is the same-the state-as compared to those of Western countries at the international level in the other hand. It is the assumption that proved their steadfastness based on data and results proven by the State beyond the socio-political movement in the beginning of 2011- in the Arab political sphere, which once again confirmed its ability to continue and survive despite the contradictions it contains. We will seek through this PHD thesis to adopt the same assumption in dealing with the phenomenon of contradiction Arab state in exchange for its ability to continue, the PHD thesis, which ruled the order of its parts within the agreed upon scientifically to search any topic to detract from the relevant organic between: language, thought and reality, If we had started with the language that proved the concept of privacy State Convention in Arabic, this situation could get the thought which gives this concept in theory, is the thought that wont turn on the reality of this paradoxical State as that thought is just a reflection of that reality, and proper diagnosis of this reality is what we thought back again, in order to open the area to restore peering around the concept of the State in case the Arabic in accordance with the priority placed by the reality of today's State within The political sphere.
Keywords: الدول- المجال السياسي العربي - نقاش حول الخلفيات والأسس